American prophecy: race and redemption in American political culture - Shulman, George M. (Univ. of Minnesota Press, 2008)
Introducing Jeremiah's legacy : placing prophecy in American politics and political theory -- Thoreau, the reluctant prophet : moral witness and poetic vision in politics -- Interlude : from Henry Thoreau to Martin Luther King Jr. and James Baldwin : race and prophecy -- Martin Luther King Jr.'s theistic prophecy : love, sacrifice, and democratic politics -- James Baldwin and the racial state of exception : secularizing prophecy? -- Toni Morrison and prophecy : "this is not a story to pass on" -- Conclusion : prophecy as vernacular political theology